Money Politics in the 2021 Election of the Head of Mekarwangi Village, Saketi District, Pandeglang Regency - Ariyan, Said; Saltum, Mutiara (Lenggogeni Data Publishing, 2025)
This study aims to analyze the practice of money politics in the 2021 Mekarwangi Village Head Election (Pilkades), Sageti District, Pandeglang Regency, as well as identify the underlying factors. Money politics is a phenomenon that continues to appear in every democratic contest at the local level and is often considered commonplace. This study uses a descriptive qualitative approach with data collection techniques through interviews, documentation, and literature studies. The results of the study show that the practice of money politics is carried out in a planned and systematic manner by the village head candidate and his successful team through the distribution of cash, basic necessities, and personal goods ahead of election day. The main factors behind the occurrence of this practice include the low economic condition of the community, the lack of political education, and the culture of money politics that has taken root in the community. This practice shows the weakness of democratic awareness and makes people pragmatic in making their political choices. Money politics not only undermines the essence of democracy, but also lowers the quality of leadership at the village level. Therefore, it is necessary to increase political education and strict supervision so that the implementation of the upcoming Regional Elections will run more cleanly and democratically.